2021
DOI: 10.2147/ahmt.s303456
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Disease Burden of Neurofibromatosis Type 1 with Plexiform Neurofibromas: A Systematic Literature Review

Abstract: Neurofibromatosis type 1 (NF1) is an incurable genetic condition that frequently includes the development of plexiform neurofibromas (PNs) in patients. A systematic literature review was conducted to identify data on the natural history, disease burden, and treatment patterns among patients diagnosed with NF1 and PN, as well as to identify evidence gaps in these areas. MEDLINE and MEDLINE In-Process, Embase, and Cochrane Library Searches were searched using predefined terms. Potential references underwent two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
(74 reference statements)
1
13
0
Order By: Relevance
“…Several targeted agents have been evaluated to ameliorate RAS hyperactivation and tumorigenesis in NF1, but the agents specifically targeting MEK/ERK have shown the most promise. 8…”
Section: Pharmacologymentioning
confidence: 99%
See 3 more Smart Citations
“…Several targeted agents have been evaluated to ameliorate RAS hyperactivation and tumorigenesis in NF1, but the agents specifically targeting MEK/ERK have shown the most promise. 8…”
Section: Pharmacologymentioning
confidence: 99%
“…Several targeted agents have been evaluated to ameliorate RAS hyperactivation and tumorigenesis in NF1, but the agents specifically targeting MEK/ERK have shown the most promise. 8 MEK 1 and 2 are homologues and upstream regulators of the ERK pathway responsible for activating cyclin D1 and subsequent cell proliferation. Selumetinib-a potent, selective, oral, ATP noncompetitive small-molecule inhibitor of both MEK 1 and 2 phosphorylation-binds to the MEK 1/2 proteins, resulting in conformational changes, cell signal transduction disruption, and arrest of tumor cell growth and proliferation.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…These worries prevented people from participating in public activities due to reluctance to leave the house (Heaney et al, 2019). In a recent systematic review, the authors concluded that a range of pNF‐related sequelae, including impaired social functioning and emotional distress, have a negative impact on quality of life (Copley‐Merriman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%